Maternal and child oral health: Report of an extension experience in academic training - Wouk, Letícia; Ferreira Silva Júnior, Manoelito; Luiz Rutz da Silva, Silvio; Lopes, Mario Cezar; do Rocio Oliveira, Marilisa; Veber, Ana Paula (Guará Journal, 2022)
This paper reports on the development of a workshop held during Operation Rondon 2018, addressing the importance of university extension for academic and future professional development. The extension initiative was planned and implemented at a health unit in the municipality of Porto Amazonas, Paraná, Brazil, by a student and professors from the State University of Ponta Grossa (UEPG). The initiative was motivated by the diagnosis of low attendance rates for prenatal dental care among pregnant women and low adherence among mothers regarding their children’s oral hygiene. Based on this information, the dentistry student developed a dynamic to investigate the participating women’s knowledge about the importance of prenatal dental care and the care of primary teeth, up until the permanent teeth of their children. A few questions were randomly posed to them and subsequently discussed to broaden their knowledge. The experience was successful, as demonstrated by the participation and curiosity of the 70 participants. Thus, it was clear that extension activities are rich in cultural diversity, develop critical thinking skills to address regional issues, and bring direct benefits to the community. Thus, they contribute to the development of individuals as citizens and professionals, and are a distinguishing feature of academic training.